Menyoal Kurikulum 2013 dalam Sistem Pembelajaran Berbasis Teknologi Informasi Guna Mengembangkan Soft Skills dan Pendidikan Karakter Anak - Rahmad Hidayat (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
To review the problem above, this article focuses on three problems; 1) what is the form of implementing Curriculum 2013 in an information technology-based learning system, 2) what are the factors that cause the neglect of the quality of soft skills and the value of children's character in this learning model, and 3) what are the implications? To examine the research problem above, the author will use Paulo Freire’s theory of